Students’ acceptance of an internet campus radio: a test of the technology acceptance model - Lahabou , Mahaman; Wok, Saodah (2011)
This study investigates Human Sciences (HS) students’ acceptance of IIUM.FM, their newly established online campus radio, by using Technology Acceptance Model (TAM) as the theoretical background. An external variable, knowledge, was added to the original model. A cross-sectional survey design was employed to gather data through a self-administered questionnaire to a sample of 467 undergraduate students to test three hypotheses generated from literature related to TAM. Both listeners (n1=238) and non-listeners (n2=229) participated in the study. The findings showed that listeners are highly knowledgeable about IIUM.FM, have positive perceptions of the radio but have a negative attitude towards listening to it. They mostly listened to music programme at night and from their hostels. Moreover, male and seniors were found to listen more frequently to IIUM.FM than female and juniors. Knowledge about IIUM.FM was found to have an influence on actual listening via Perceived Ease of Listening (PEOL), Perceived Usefulness of Listening (PUOL), and attitude towards listening. For the non-listeners, the reasons for not listening were lack of time, reception problems, and lack of knowledge on the existence of IIUM.FM. However, they expressed their intention to listen to it in the future.